2020
DOI: 10.1038/s41598-020-65136-4
|View full text |Cite|
|
Sign up to set email alerts
|

DNA-based identification of predators of the corallivorous Crown-of-Thorns Starfish (Acanthaster cf. solaris) from fish faeces and gut contents

Abstract: The corallivorous Crown-of-Thorns Starfish (CoTS, Acanthaster spp.) has been linked with the widespread loss of scleractinian coral cover on Indo-Pacific reefs during periodic population outbreaks. Here, we re-examine CoTS consumption by coral reef fish species by using new DNA technologies to detect Pacific Crown-of-Thorns Starfish (Acanthaster cf. solaris) in fish faecal and gut content samples. CoTS DNA was detected in samples from 18 different coral reef fish species collected on reefs at various stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 49 publications
(117 reference statements)
2
27
0
Order By: Relevance
“…These results, and those of previous studies, suggest that current zoning arrangements act a means of moderating the impact of an active COTS outbreak, and that its role in a COTS Control Program will be as a complementary action used to support manual control or where manual control cannot be employed. The management utility of observed zoning effects on COTS populations is also compromised by the current lack of a mechanistic understanding of how such effects actually occur; whether directly through predation by targeted fish species 46 or indirectly through cascading trophic or behavioural effects, and whether the main effects are on the pelagic or settled phase or both 34 , 47 . Determining the role of MPAs, and, in particular, the level of take of various fisheries on the GBR, on COTS densities and population outbreaks is a focus of current work.…”
Section: Resultsmentioning
confidence: 99%
“…These results, and those of previous studies, suggest that current zoning arrangements act a means of moderating the impact of an active COTS outbreak, and that its role in a COTS Control Program will be as a complementary action used to support manual control or where manual control cannot be employed. The management utility of observed zoning effects on COTS populations is also compromised by the current lack of a mechanistic understanding of how such effects actually occur; whether directly through predation by targeted fish species 46 or indirectly through cascading trophic or behavioural effects, and whether the main effects are on the pelagic or settled phase or both 34 , 47 . Determining the role of MPAs, and, in particular, the level of take of various fisheries on the GBR, on COTS densities and population outbreaks is a focus of current work.…”
Section: Resultsmentioning
confidence: 99%
“…Cheilinus undulatus shapes benthic communities via predation on mollusks, crustaceans, and echinoids, including the crown of thorns starfish (Cowan et al, 2017;Kayal et al, 2012;Kroon et al, 2020;Randall et al, 1978), while B. muricatum is the most important bioeroder and the largest coral predator (Bellwood & Choat, 2011), holding a keystone role in the maintenance of coral community structure and stability of coral reefs (Bellwood et al, 2012). Consistent with previous studies that used underwater visual census techniques in shallow water, our study using BRUVS identified high abundances of these large iconic labrids at the Rowley Shoals and relatively low abundances at other atolls and islands (Bellwood et al, 2012;Edgar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The predatorremoval hypothesis proposes that overfishing has released COTS from top-down control [14]. This is supported by findings that a suite of target (fished) and non-target species prey on COTS gametes, larvae, juveniles, and adults [15][16][17], and that marine protected areas which would be expected to have a more intact fish guild are less prone to outbreaks [18][19][20]. Finally, as periodic outbreaks appear to be an inherent feature of COTS, it has been hypothesised that these are also a natural phenomenon [21] and, as the larvae evolved in oligotrophic tropical waters, the larval-resilience hypothesis posits that they are naturally resilient to food limitation [22,23].…”
Section: Introductionmentioning
confidence: 96%